Pelatihan Bahasa Inggris dan Pengelolaan Mangrove untuk Pemberdayaan Karang Taruna dalam Pengembangan Objek Wisata Mangrove - Mirna Yunita; Yuneva Yuneva; Fevi Wira Citra; Elva Utami; Warsa Sugandi; Zairin Zairin; Muhammad Alfi (Abdihaz: Jurnal Ilmiah Pengabdian pada Masyarakat, 2021)
Training of English Language and Mangrove Management for Youth Empowerment in Mangrove Tourism Object Development Karang taruna is a youth organization in a village. This community service program was aimed to train Karang Taruna member in Sumber Jaya Village, Kota Bengkulu speaking English which can be used to guide foreign tourists and and to educate them about mangroves and its management for ecotourism activities. The activity was carried out in three stages: 1) the preparation; 2) the planning; 3) the implementation stage. In the third stage, an evaluation was carried out through the practice of speaking English and distributing questionnaires about English language skills and knowledge about mangroves. After the service activities were carried out, the results showed that the participants: 1) 100% understood how to greet and introduce in English; 2) 90% could explain the information about interest place in English; 3) 90% could ask and answer in English; 4) 100% could explain about tourism object in English; 5) 100% could explain about the rules of travel in English; 6) 100% could answer about tourism object; 7) 100% could convey likes and dislikes; 8) 100% could hosting; 9) 90% could explain how to make organic fertilizers; 10) 90% could explain the making of handicrafts; 11) 100% understood the function, potential and types of mangrove forests; 12) 90% knew the tourism management based on mangrove conservation; 13) 90% understood maintenance and improvement of mangrove quality; 14) 100% understood management through tourism diversification; 15) 90% understood mangrove tourism infrastructure; 16) 100% understood the potential of mangroves that can be processed into souvenirs. The results of the service can be concluded that the Karang Taruna members have understood about English language technique specifically to tour guide and had an understanding of mangroves.